2015
DOI: 10.1016/j.envres.2015.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of myocardial infarction by increased ambient fine particle concentration: Effect modification by source direction

Abstract: Background Previously, we reported a 18% increased odds of ST-elevation myocardial infarction (STEMI) associated with each 7.1 µg/m3 increase in PM2.5 concentration in the hour prior to MI onset. We found no association with non-ST elevation myocardial infarction (NSTEMI). We examined if this association was modified by PM2.5 source direction. Methods We used the NOAA HYbrid Single-Particle Lagrangian Trajectory (HYSPLIT) model to calculate each hourly air mass location for the 24 hours before each case or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For example, the risk of CVD ED visits associated with increased OC concentrations had an increasing trend over time, which coincided with the increasing percentage of OC in PM 2.5 total mass (OC was the only major component with an increasing percentage of PM 2.5 total mass over time). An increasing percentage of OC might include both reactive oxygen species and species with oxidative potential, which could potentially result in increased oxidative stress and exacerbation of cardiorespiratory diseases (Hopke et al 2015). Previous studies conducted in New York State also suggested that secondary OC could be a key component leading to temporal changes in the risk of adverse health outcomes associated with PM 2.5 as oxidative stress is associated more with secondary organic aerosols Hopke et al 2019;Zhang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the risk of CVD ED visits associated with increased OC concentrations had an increasing trend over time, which coincided with the increasing percentage of OC in PM 2.5 total mass (OC was the only major component with an increasing percentage of PM 2.5 total mass over time). An increasing percentage of OC might include both reactive oxygen species and species with oxidative potential, which could potentially result in increased oxidative stress and exacerbation of cardiorespiratory diseases (Hopke et al 2015). Previous studies conducted in New York State also suggested that secondary OC could be a key component leading to temporal changes in the risk of adverse health outcomes associated with PM 2.5 as oxidative stress is associated more with secondary organic aerosols Hopke et al 2019;Zhang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In Sun's studies, the average concentration of PM 2.5 from 1999 to 2011 was 37 mg m À3 in Hong Kong (Sun et al, 2015). In New York (USA), the mean PM 2.5 concentration was only 8 mg m À3 (Hopke et al, 2015), which is far lower than that in Tianjin. Knowing this, there are still many actions to be taken to reduce PM 2.5 emissions.…”
Section: Resultsmentioning
confidence: 93%
“…In Europe, CVD is the cause of nearly half (45%) of all deaths [1]. Recently, studies throughout the world have been connecting the emergence of the CVD with air pollution levels [2][3][4][5][6]. Increased levels of air pollutants constitute an additional risk factor for CVD, especially in metropolitan areas [7].…”
Section: Introductionmentioning
confidence: 99%